A Literature Review on Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis and its Complications - Marium Ali; Ibram Zaki; Shamail Zia; Muhammad Haseeb; Rahul Pawate; Meeran Asher Syed; Muhammad Naveed Uz Zafar; Vardah Zia; Syed Jawwad Ali; Fazail Zia; Farozaan Shamail (Journal of Liaquat National Hospital, 2023)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are delayed-type hypersensitivity reactions to medications. Early signs of identification and proper management are critical for patients’ survival. The distinct features initially resemble influenza-like conditions, malaise, and fever with gradual pain and lesions in the oral, ocular, and genital areas along with other systemic symptoms. SJS/TEN can be differentiated: SJS by the degree of skin involvement and TEN by the degree of exfoliation. In SJS, skin involvement is < 10%, whereas in TEN, skin involvement is > 30%; overlapping among the two develops with 10–30% skin involvement. For the identification of culprit drugs, oral provocation tests, patch testing, and in vitro assay tests are used. The estimation of mortality rates for SJS/TEN has been performed by using SCORTEN- severity-of-illness score for toxic epidermal necrolysis. Sulfonamides, anti-epileptics, NSAIDs (oxicams), and allopurinol are some of the medications with a high risk of SJS/TEN development. Drug-mediated SJS/TEN is facilitated by genetic involvement particularly HLA antigens along with CYP450 genetic variants. Most frequent clinical features include mucosal involvement of nasopharyngeal, esophageal, and genital regions accompanying blisters and erosions. A multidisciplinary approach is required for the handling and treatment of SJS/TEN. It is mandatory to withdraw the contributing medicine followed by supportive therapy. Clinical management involves the use of corticosteroids, cyclosporine, and immunoglobulins.